2019
DOI: 10.1021/acsomega.9b01482
|View full text |Cite
|
Sign up to set email alerts
|

Delineating the Biofilm Inhibition Mechanisms of Phenolic and Aldehydic Terpenes against Cryptococcus neoformans

Abstract: The recalcitrant biofilm formed by fungus Cryptococcus neoformans is a life-threatening pathogenic condition responsible for further intensifying cryptococcosis. Considering the enhanced biofilm resistance and toxicity of synthetic antifungal drugs, the search for efficient, nontoxic, and cost-effective natural therapeutics has received a major boost. Phenolic (thymol and carvacrol) and aldehydic (citral) terpenes are natural and safe alternatives capable of efficient microbial biofilm inhibition. However, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 71 publications
1
32
0
2
Order By: Relevance
“…In fact, they are able to react with peroxyl radicals, as demonstrated by Origanum vulgaris essential oil, whose most relevant compounds are thymol and carvacrol [ 9 , 12 ], Thimus capitatus essential oil, whose most relevant compound is still carvacrol [ 25 ], and many others [ 35 , 36 ]. A comparable antioxidant activity was also exerted by the citral loaded liposomes due to citral, an aldehydic terpene [ 37 ], as previously reported [ 38 , 39 , 40 ].…”
Section: Discussionsupporting
confidence: 78%
“…In fact, they are able to react with peroxyl radicals, as demonstrated by Origanum vulgaris essential oil, whose most relevant compounds are thymol and carvacrol [ 9 , 12 ], Thimus capitatus essential oil, whose most relevant compound is still carvacrol [ 25 ], and many others [ 35 , 36 ]. A comparable antioxidant activity was also exerted by the citral loaded liposomes due to citral, an aldehydic terpene [ 37 ], as previously reported [ 38 , 39 , 40 ].…”
Section: Discussionsupporting
confidence: 78%
“…Similarly, in Cryptococcus neoformans , citral, thymol and carvacrol reduced the ergosterol content at their inhibitory concentrations (Kumari et al . 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of action of phenolics against microbial targets could ascribe to several effects including destabilization of the plasma membrane, modification of cellular permeability, inhibition of microbial enzymes and inactivation of efflux pumps [ 30 , 42 ]. Kumari et al [ 43 ] reported that phenolics are capable of disrupting biofilm cell surface leading to an elevation in cell roughness and reduction in cell height. In a molecular docking study, Perez-Castillo et al [ 44 ] reported the antifungal activity of cinnamic acid derivatives against Candida strains and identified that the compounds can bind to multiple targets.…”
Section: Discussionmentioning
confidence: 99%